Green transformation: Lessons from the fuel cell innovation system in Taiwan. (10th December 2019) - Chou, Justin Che-Ping; Hu, Mei-Chih; Tsung-Ying Shih, Tommy
Abstract: This study applies the technological innovation system framework to the case of the fuel cell sector in Taiwan. Many Asian latecomers, such as Taiwan, tend to adopt a top-down approach to emphasize the importance of environmental issues but the result is limited. We aim to take Taiwan's fuel cell innovation system as an example to explore why Taiwan has formulated a technological innovation system to engage universities, research institutes, and firms to undertake R&D and entrepreneurial activities, but the results are still limited with respect to innovation and commercialization. This paper identifies the problems and challenges in Taiwan's fuel cell innovation system by using an embedded case study to illustrate the strengths and weaknesses of the systems in seven system functions. The study contributes to the increased understanding for the development of renewable energy from the perspective of latecomer nations whereas the mechanism behind technological transition and the strategies of actors within technological innovation systems deserve closer attention.